Development of aerobic-anaerobic performance in wrestlers using interval runs - Pashintsev, V. G. (International Journal of Wrestling Science, 2014)
It can be argued that the development of the aerobic- anaerobic endurance component using interval running creates a load for the fighter with an average heart rate of just below 170 beats / min, increasing blood lactate to 6.9 mmol / l, which leads to a decrease in pulmonary and bronchial passage capacity and increasing maximum ventilation by 9.2%.